Assessment of Polish real estate funds liquidated at planned dates - Artur Arkadiusz Trzebinśki (The Central European Review of Economics and Management (CEREM), 2017)
Aim: The purpose of this article is to assess the efficiency of management of real estate funds by managers and profitability of funds.Design / Research methods: The study used elements of financial analysis and case studies.Conclusions / findings: The results of the survey indicate the low yields of the real estate funds surveyed (only one fund brought profits to the investors, the remaining 5 losses) and the low efficiency of the managers and the high cost-of-operation of the real estate funds. The research has shown the low effectiveness of investment strategies and business models that require changes and other solutions.Originality / value of the article: The study covered the real estate funds that were liquidated or liquidated started in the managerial terms, which allows to assess the effectiveness of managers at every stage of life funds. The research is a continuation of the author's earlier research. According to author's knowledge, no similar studies have been published so far. – – Aim: Celem artykułu jest ocena sprawnosći zarzadzania funduszami nieruchomosći przez zarzadzajacych i dochodowosćf́unduszy.Design / Research methods: W badaniu wykorzystano elementy analizy finansowej i studia wybranych przypadkoẃ.Conclusions / findings: Rezultaty badania wskazuja na niska dochodowosćb́adanych funduszy nieruchomosći (tylko 1 fundusz przyniośł inwestorom zysk, natomiast pozostałe 5 strate) oraz niska sprawnosćźarzadzajacych i wysoka kosztochłonnosćṕrowadzonej działalnosći przez fundusze nieruchomosći. Przeprowadzone badania wskazuja na niska skutecznosćśtosowanych strategii inwestycyjnych i modeli biznesowych, ktoŕe wymagaja zmian i zastosowania innych rozwiazan\'.Originality / value of the article: Badaniem objeto fundusze nieruchomosći, ktoŕe zostały zlikwidowane lub likwidacje rozpoczeto w przyjetym przez zarzadzajacych terminie, co pozwala na ocene sprawnosći zarzadzajacych na kazḋym etapie zẏcia funduszy. Badania stanowia kontynuacje wczesńiejszych badanáutora. Według wiedzy autora nie opublikowano do tej pory zblizȯnych badan\'.
Keywords: G17; G23; 330; real estate mutual funds; profitability of real estate funds; efficiency of investment fund management